2017
DOI: 10.1038/s41598-017-05708-z
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Dinitrogen as A Dipolarophile in 1,3-Dipolar Cycloadditions: A Theoretical Study Using Nitrile Imines as “Octet” 1,3-Dipoles

Abstract: Theoretical calculations at the G4MP2 level of theory demonstrate that it is possible to activate dinitrogen to make it react in dipolar cycloadditions using neutral beryllium derivatives and other neutral metallic compounds. For the particular case of beryllium, the barrier decreases more than 40 kJ·mol–1 with respect to the non-catalysed reaction. The activation achieved is lower than using diazonium salts (models of protonated N2), but still in a range that can be experimentally attainable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The beryllium bond is one of the strongest NCIs between neutral molecules. It produces important changes in the properties of the molecules involved in the interaction, such as a significant increment of the acidity of the interacting systems, , a change in the nature of the halogen bond in ternary complexes, a spontaneous production of radicals, as well as having the possibility to act as a catalyst . In addition, the importance and biological implications of the π-hole in beryllium bonds have been explored in the literature …”
Section: Introductionmentioning
confidence: 99%
“…The beryllium bond is one of the strongest NCIs between neutral molecules. It produces important changes in the properties of the molecules involved in the interaction, such as a significant increment of the acidity of the interacting systems, , a change in the nature of the halogen bond in ternary complexes, a spontaneous production of radicals, as well as having the possibility to act as a catalyst . In addition, the importance and biological implications of the π-hole in beryllium bonds have been explored in the literature …”
Section: Introductionmentioning
confidence: 99%
“…Because it is a through space-effect, CFGs can also be incorporated into an external catalyst, analogous to our work with Diels−Alder reactions. 31 Alternatively metal complexation is another potential strategy to harness these electrostatic effects, and in this respect, we note that Lewis acid complexation has been used to increase the rate of the reverse reaction, 34 and the associated transition-state stabilization would also increase the forward reaction. Finally, we note that combinations of CFGs and other barrier-lowering strategies could yield further improvements in rate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[ 191 ] Given the broad applicability and practicality of this tactic, there is no doubt that these reactions will find wide implications in tetrazole chemistry, meanwhile in‐depth mechanistic study and divergent regio‐control are also suggested to be put on the agenda. [ 192,193 ]…”
Section: Cyclization and Cycloaddition Reactions For The Constructionmentioning
confidence: 99%